2015
DOI: 10.1371/journal.pone.0138452
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cell Death in Regorafenib-Treated Experimental Colon Carcinomas Using Annexin-Based Optical Fluorescence Imaging Validated by Perfusion MRI

Abstract: ObjectiveTo investigate annexin-based optical fluorescence imaging (OI) for monitoring regorafenib-induced early cell death in experimental colon carcinomas in rats, validated by perfusion MRI and multiparametric immunohistochemistry.Materials and MethodsSubcutaneous human colon carcinomas (HT-29) in athymic rats (n = 16) were imaged before and after a one-week therapy with regorafenib (n = 8) or placebo (n = 8) using annexin-based OI and perfusion MRI at 3 Tesla. Optical signal-to-noise ratio (SNR) and MRI tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Molecular changes play an important regulatory role in the development of malignant tumors. Cell surface Connexins or membrane proteins can induce the transcription initiation activity of downstream oncogenes, which promotes aberrant activation of the cell cycle in colonic epithelial cells and leads to excessive proliferation of cancer cells[ 14 ]. Accumulating experimental data indicate that phosphatidylserine exposition is associated with apoptosis and other cell death programs[ 15 - 17 ], which renders it an attractive target in imaging overall cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular changes play an important regulatory role in the development of malignant tumors. Cell surface Connexins or membrane proteins can induce the transcription initiation activity of downstream oncogenes, which promotes aberrant activation of the cell cycle in colonic epithelial cells and leads to excessive proliferation of cancer cells[ 14 ]. Accumulating experimental data indicate that phosphatidylserine exposition is associated with apoptosis and other cell death programs[ 15 - 17 ], which renders it an attractive target in imaging overall cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, approaches aiming to image whole-tumour apoptosis for the purposes of assessing therapeutic response (to chemotherapy, targeted therapies, and radiotherapy) were embraced. These imaging methods include MRI [ 20 , 33 ], magnetic resonance spectroscopy (MRS) [ 34 ], USS [ 35 ], novel fluorescence imaging [ 36 ], scintigraphy [ 11 , 18 ] and PET [ 6 , 10 , 16 , 17 ]. Studies using [ 99m Tc]Annexin V, in particular, led the way for nuclear imaging of apoptosis [ 11 , 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a handful of pre-clinical and clinical PET imaging studies attempting to image molecular and biochemical events of the apoptotic process [ 6 – 14 ]. Studies with [ 18 F]ML-10 [ 9 , 15 17 ] and [ 99m Tc]Annexin V [ 11 , 12 , 18 – 20 ] showed promising results in humans. A study of [ 18 F]ML-10 [ 9 ] — a member of the aposense family of biomarkers that measures ‘apoptotic imprint’ — in human subjects reported favourable dosimetry and biodistribution, and binding to apoptotic sites in testicular tissue of mice, confirmed by terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) of apoptotic cells; initial studies reported correlation of early changes of tumour [ 18 F]ML-10, and later changes in anatomical tumour dimension following radiotherapy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been suggested to address these potential confounding factors for interpreting therapeutic response using apoptosis imaging, including diffusion-weighted MR imaging ( 20 ), perfusion MR imaging ( 21 ), and acquiring an 18 F-labeled fluorodeoxyglucose PET scan ( 2 ). In this report, we show another approach to assess the presence of viable tumor cells at the time of [ 18 F]ML-10 PET using 23 Na MRI.…”
Section: Discussionmentioning
confidence: 99%